Synthesis of Metal and Metal Oxide Nanoparticles Using Plant Extract: a Review - Is Fatimah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
Nanotechnology is an emerging technology and it is related to various applications. Related to nanotechnology development, the use of green chemistry concept, low cost technology and sustainability is a must. Synthesis of nanoparticles using plant extract is a developing technique within the scheme. In this paper, study on metal/metal oxide synthesis and its aspects is presented for describing the potency of natural resources for nanoparticle synthesis within green chemistry approach.